Penggunaan Ragam Bahasa Bali Pada Bahan Ajar "Bahasa Lan Sastra Bali" SD Kelas V - Ida Ayu Sukma Wirani; Ida Bagus Made Ludy Paryatna; Ida Bagus Rai; Putu Dewi Merlyna Yuda Pramesti (Dharma Sastra: Jurnal Penelitian Bahasa dan Sastra Daerah, 2022)
This study aims to determine the variety of languages used in Balinese language textbooks for fifth grade elementary school in Singaraja. The variety of Balinese languages has a level of use in communicating. The variety of languages used in teaching materials will affect the readability of the text used by students in learning. The level of difficulty in understanding reading material that greatly affects students' understanding in learning. The variety of languages used in the Class V SD textbooks can be reached by students well. There are some words that are still difficult for students to reach, such as carem, prawantaka, manggala, ninggilang, madurgama, etc. This is in the evaluation of teaching materials. The text contained in the teaching materials already uses a variety of andap languages that can be reached by students who have a background in everyday language, namely Balinese. These teaching materials have been effectively used because their presentation is simple and easy to reach, but they still need assistance for children who speak Indonesian